024 Tackle characteristics associated with concussion in British university level rugby union. (3rd March 2020) - Roberts, Simon; Kemp, Simon; Morgan, Luke; Stokes, Keith
Abstract : Background: Understanding the risk of concussion and how this injury occurs in rugby union match play can inform future injury reduction strategies. This has been investigated in professional rugby but not in the UK elite level pathway. Objective: Describe the incidence of concussion and characteristics of tackles resulting in concussion in British University rugby union. Design: A one-season prospective cohort study; team medical staff reported match play concussions. Matches were filmed and tackle-related concussions were analysed alongside 796 non-injurious 'control' tackles. Setting: British University and Colleges (BUCS) 'Super' rugby union: season 2018/19. Participants: Eight teams (341 players). Independent variables: Match exposure. Main outcome measurements: Injury incidence and characteristics of tackles associated with concussion. Results: There were 43 concussions in 154 team games; incidence was 14.0 per 1000 player match hours (95% CI: 10.1–18.8) and mean absence was 23 days (95% CI: 16.1–29.9). Thirty-four (79%) concussions occurred in the tackle; 22 by the tackler and 12 by the ball carrier. Twenty-five tackles resulting in concussion could be conclusively identified on video (tackler: 16; ball carrier: 9). For control tackles, 5% resulted in initial impact to the head/neck and 18% to the shoulders of the ball carrier compared with tackles resulting in concussions to the ball carrier [head/neck, 3 (33%); shoulder, 2 (22%)] or tackler [head/neck, 2 (13%); shoulder, 3 (19%)]. For tackler concussions, 3 (19%) involved head-to-head contact (2% of control tackles) and 4 (25%) involved head-to-shoulder contacts (6% of control). The ball carrier was travelling at high speed for 67% of ball carrier concussions, compared with 29% for control tackles. Conclusions: Concussion incidence in high-level university rugby union is slightly lower than professional rugby with most concussions occurring in the tackle. Lowering tackle height may help reduce concussion for the ball carrier and the tackler should prioritise head positioning away from the ball carrier's head and shoulders.